Tuberculosis survivors and the risk of cardiovascular disease: analysis using a nationwide survey in Korea - Yang, Jiyoul; Kim, Sun-Hyung; Sim, Jae Kyeom; Gu, Seonhye; Seok, Jeong Won; Bae, Dae-Hwan; Cho, Jun Yeun; Lee, Ki Man; Choe, Kang Hyeon; Lee, Hyun; Yang, Bumhee; Min, Kyung Hoon (Frontiers in Cardiovascular Medicine, 2024)
Background Although the association between tuberculosis (TB) and cardiovascular disease (CVD) has been reported in several studies and is explained by mechanisms related to chronic inflammation, few studies have comprehensively evaluated the association between TB and CVD in Korea. Methods Using the Korea National Health and Nutrition Survey (KHNANES), we classified individuals according to the presence or absence of previous pulmonary TB was defined as the formal reading of a chest radiograph or a previous diagnosis of pulmonary TB by a physician. Using multivariable logistic regression analyses, we evaluated the association between the 10-year atherosclerotic cardiovascular disorder (ASCVD) risk and TB exposure, as well as the 10-year ASCVD risk according to epidemiological characteristics. Results Among the 69,331 participants, 4% (n = 3,101) had post-TB survivor group. Comparing the 10-year ASCVD risk between the post-TB survivor and control groups, the post-TB survivor group had an increased 10-year ASCVD risk in the high-risk group (40.46% vs. 24.00%, P < 0.001). Compared to the control group, the intermediate- and high-risk groups had also significantly increased 10-year ASCVD risks (odds ratio [OR] 1.14, 95% confidence interval [CI] 1.04–1.23 and OR 1.69, 95% CI 1.59–1.78, respectively) in the post-TB survivor group. In the association of CVD among post-TB survivors according to epidemiologic characteristics, age (adjusted OR [aOR] 1.10, 95% CI 1.07–1.12), current smoking (aOR 2.62, 95% CI 1.32–5.17), a high family income (aOR 2.47, 95% CI 1.32–4.62), diabetes mellitus (aOR 1.92, 95% CI 1.20–3.07), and depression (aOR 2.15, 95% CI 1.10–4.19) were associated with CVD in the post-TB survivor group. Conclusions Our study findings suggest a higher 10-year ASCVD risk among TB survivors than healthy participants. This warrants long-term cardiovascular monitoring and management of the post-TB population.